Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Konsumen Di Alfamart Marchelia Batam - Reny Wilija Sihite; Nora Pitri Nainggolan (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
On this research is that there are a lot of criticism of quality service and a mismatch promotional programs. This research aims to review a causal link variable quality of services and promotion of customer satisfaction. This study using methods with techniques associative causal method associative causally.Data collection techniques using a technique the spread of a questionnaire that spread to 194 respondents. The result of this research for the quality of services t.hitung 5,709 > t.tabel (1,972) and Variable promotion t.hitung 3,706 > t.tabel (1,972). the result uji t variable concluded that the promotion it has some positive effects and significantly to customer satisfaction. The result of f.hitung 98,307 > f tabel (2,64) be concluded this hypothesis accepted and declared simultaneous between variables quality of services and variable promotion simultaneously influential positive and significant on variables customer satisfaction.